Assessment and enhancement of the performance level of an algerian company - Hichem Aouag; Mohyiddine Soltani; Mohammed Djamel Mouss (My University, 2019)
The work presented in this paper investigates an application of Six Sigma approach for the purpose of assessment of the competitiveness capability of an Algerian company through a period of three years. To do this we use a weighted DPMO and Six Sigma level approaches. Firstly the weighted DPMO was used to calculate the proportion of quality defects. Secondly, Sigma level was introduced to evaluate the competitiveness of the company. The proposed methodology is applied in a real case study, the obtained results are discussed.
Intervention
Keywords: Six Sigma; DPMO; Sigma level; weighted DPMO.